Łódź leisure time space as perceived by liceum students and members of the ‘Universities of the Third Age’ - Duda, Michał (Turyzm/Tourism, 2015)
The article is a summary of research into the perception of leisure time space, conducted in 2014 among Liceum students (aged 16-19) and members of the ‘Universities of the Third Age’ (U3A) in Łódź. The author compared perceptions of the idea of leisure time by both of these groups, studied how they spent it and described the factors which have a significant influence. Next, he analysed different approaches to the urban space of Łódź as well as comparing them to the spatial range and the types of visited places and events.